Comparison of the mechanical properties of milk fouling and whey protein fouling. Issue 1 (18th November 2019) - Liu, Jintian; Wiese, Hanna; Augustin, Wolfgang; Scholl, Stephan; Böl, Markus
Abstract: The formation of fouling deposit is a significant problem for the dairy industry. Many experimental analyses have been carried out to explore the cleaning process using whey protein solution as a surrogate material because the main fouling components in milk are whey proteins. In view of mechanical cleaning processes, the mechanical behaviour of milk and whey protein fouling is compared using indentation and relaxation experiments and material parameters of a visco‐hyperelastic model are determined using an inverse finite element method (FEM).